Implementation of Physics Learning Materials Based Generative Learning With Open-Ended Problem Approach To Stimulate Critical Thinking Skills - Chichi Rahayu; Eliyarti Eliyarti (JIPF (Jurnal Ilmu Pendidikan Fisika), 2019)
The subject of this research was to discribe the implementation physics learning materials based generative learning with open-ended problem approach to stimulate students' critical thinking skills. This type of research is 4D consisting of four stages, in this paper discussing a review of the implementation which includes in development stage. The  data collection instruments are essay tests, assessment sheets, and student competency sheets. Analysis technique carried out in three domain:cognitive design assessment uses the t test with sub-scale analysis of critical thinking, also using gain test analysis to see an increase in critical thinking, then the analysis for affective and psychomotor domains using descriptive statistics. Based on analysis of student’s competency critical thinking skills increased by 29.9%. with tcount19.06>t(0.975)(31)1.67 in significance level 0.05, also gain factor from the 1st meeting until 4th meeting are 1=0.3,2=0.4,3=0.5,4=0.5 in an interval 0.3<g<0.7 indicating significant differences. It means by using this learning material student can increase their critical thinking skill. In the affective domain, the attitudes of the learner in good categories with a class average of 76.65% and competency skills get an average of 74.18%, placing this material can improve learners learning outcomes in affective competencies and skills.